HEMORRHAGIC STROKE - SYMPTOMS AND TREATMENT - Omonov Sherzod Urol ugli; Abuvova Dilrabo Buriboyevna; Mavlonova Mehrangiz Sodiqovna; Jumakulov Aslam Asqar ugli; Kasimov Arslanbek Atabayevich; Mamurova Mavludakhon Mirkhamzayevna (Western European Studies, 2024)
Hemorrhagic stroke (Hemorrhagic stroke) is a hemorrhage in the gray or white matter of the brain that occurs due to ruptured blood vessels. It is also known as intracerebral hemorrhage. In such an acute and dangerous disorder, blood accumulates, presses on the surrounding brain tissue and damages it, which threatens disability. But if help is given in time, irreversible consequences can be prevented and a person's life can be saved.
Keywords: hemorrhagic stroke; impaired cerebral circulation